Theoretical and experimental analysis of surface anchoring in the surface stabilization of ferroelectric liquid crystal cells - Rihab Zgueb; Hassen Dhaouadi (Capillarity, 2024)
Based on the response of a chiral smectic liquid crystal to electrical excitation, this paper develops a theoretical calculation to explain the observed phenomenon in a confined structure, with the aim to establish a connection between these phenomena and the surface anchoring energy. To demonstrate the influence of surface anchoring on the observed phase behaviors in the surface stabilization of ferroelectric liquid crystal cells, an experimental validation of the theoretical calculations is conducted. Importantly, it is possible to express the transition thermal shift as a function of the anchoring energy by calculating this energy as a function of the square of the tilt angle. Our calculations allow for the utilization of experimental outcomes in determining distinctive parameters such as the anchoring energy and the elastic constant, two quantities that are essential for understanding and controlling ferroelectric liquid crystal devices. Document Type: Original article Cited as: Zgueb, R., Dhaouadi, H. Theoretical and experimental analysis of surface anchoring in the surface stabilization of ferroelectric liquid crystal cells. Capillarity, 2024, 11(2): 31-40. https://doi.org/10.46690/capi.2024.05.01